Protective factors contributing to the health status of construction industry migrant workers in Chinese mainland - Yuxiu Bai; Yingying Lin; Daokai Sun; Chuanjing Liao; Min Zhang; Rufang Ye (Scientific Reports)
Abstract Construction industry migrant workers (CIMWs) face high-intensity labor and harsh working environments, experiencing significant health issues. Studying these health issues can help to protect workers’ rights, improve labor efficiency, and promote sustainable development in the construction industry. The objective of this study is to analyze the relationships among health status, social support, and marital adjustment in construction migrant workers. Data were collected from 446 migrant workers who completed the Self-rated Health Measurement Scale (SRHMS), Marital Adjustment Test (MAT), and Social Support Rating Scale (SSRS). The results showed that (1) CIMWs were in poor social health, with low social support but good marital adjustment. (2) The higher the education level and monthly income, the better the social health. (3) The scores on the SRHMS had a significant positive correlation with the scores on the MAT and SSRS, and there were significant differences in SRHMS scores among the different levels of marital adjustment. (4) Education level, subjective social support, utilization of support, and marital adjustment significantly predicted overall health status. (5) Marital adjustment directly predicted mental health and social health, and also had an indirect relationship through social support. Education level had direct and indirect predictive effects via social support on social health. Social support fully mediated the association between education level and mental health. (6) Education level, marital adjustment, and social support were all protective factors contributing to the health status of CIMWs.